0.5 Mb Array as a First‐Line Prenatal Cytogenetic Test in Cases without Ultrasound Abnormalities and Its Implementation in Clinical Practice. Issue 9 (6th June 2013) - Srebniak, Malgorzata I.; Mout, Lisanne; Van Opstal, Diane; Galjaard, Robert‐Jan H.
<x xml:space="preserve">Abstract</x> Based on our experience and the results presented here, we recommend performing rapid array testing as a first‐tier test in all cases referred for invasive prenatal diagnosis by using the same array platform and performing high resolution analysis in cases of ultrasound abnormalities and 0.5Mb analysis for other indications. A 0.5Mb resolution shows a high diagnostic potential and significantly minimizes the number of VOUS. It can detect the well‐known microdeletion syndromes including the atypical 22q11 microdeletion presented on the image. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>